Stakeholder Prioritization in Brazilian Companies Disclosing GRI Reports - Keysa Manuela Cunha de Mascena; Adalberto Americo Fischmann; João Maurício Gama Boaventura (BBR: Brazilian Business Review)
This study aimed to describe the stakeholder prioritization in Brazilian companies and their relationship with the industry. In this research, prioritization is operationally defined as the preferential treatment to the interests of one stakeholder over another. The sample is composed of 90 companies with sustainability reporting adopting the Global Reporting Initiative (GRI) framework. We used the Mann-Whitney test to compare the level of treatment with the interests of internal and external stakeholders. We confirmed the hypotheses that the internal stakeholder has a higher level of treatment and that the level of treatment is influenced by characteristics of the industries. This study presents as theoretical contribution the analysis of the industry factor in stakeholders prioritization. Understanding the mechanisms of stakeholders prioritization is important for the manager to encourage relevant stakeholders to the achievement of the company's goals in its sector.